Penggunaan Media Pop-Up Book Berbasis Komik Untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Pendidikan Kewarganegaraan Kelas III Mi Ma’arif Kliwonan Wonosobo - Masruroh, Umi Sofiyatun; Aziz, Noor; Firdaus, Firdaus (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
The aims of this study were to: 1) find out the differences in learning outcomes between students who used comic-based pop-up book media and students who did not; 2) To find out whether comic-based pop-up book media can improve learning outcomes in class III citizenship education subjects that apply comic-based pop-up book media. This research uses a type of quantitative experimental research (quasi-experimental research). The design used in this research is one group pretest-posttest. This research was conducted at MI Ma'arif Kliwonan Wonosobo. There were two samples in this study: the experimental class consisted of 28 students and the control class consisted of 26 students. In this study using observation, tests and documentation to collect data. Meanwhile, the data analysis technique used prerequisite test and hypothesis test. The results of this study show: 1) The calculation of the hypothesis test states that there are differences in student learning outcomes in civics education subjects, namely 11,150 > 2,006 with a significance level of 5% and 11,150 > 2,673 with a significance level of 1%; 2) The increase in pretest and posttest results was carried out by calculating the N-Gain test in the experimental class of 0.774 in the high category.